Implementation of Entry Age Normal and Projected Unit Credit Methods in Pension Fund Calculation - Harahap, Tua Halomoan; Maysarah, Maysarah; Alisawi, Wisam Ch.; Jabbar, Abeer H.; Muhammad, Faisal (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Pension funds are financial assets provided to individuals who have retired due to reaching retirement age. PT. Pasifik Arta Indonesia, a company established in Medan for approximately five years, lacks a comprehensive understanding of pension funding, specifically concerning normal contributions and actuarial obligations for employees and agencies using the EAN and PUC methods. This study aims to provide an overview of pension fund calculations at PT. Pasifik Arta Indonesia by comparing the two methods. The results show that normal contributions under the PUC method increase with the length of service, whereas the EAN method maintains constant contributions regardless of service length. Both methods share a common trait: the younger the employee at the time of hiring, the lower the normal contribution. Regarding actuarial obligations, both methods exhibit increasing values with longer service, with the EAN method resulting in higher obligations compared to the PUC method.